Pengembangan Modul Menulis Cerpen Menggunakan Model PBL Pada Mata Kuliah Apresiasi Prosa - Zhe, Zherry Putria Yanti; Gusriani, Atika; Yuniarti, Lisa (LP. Ma'arif Janggan Magetan, 2022)
This research is motivated by initial refrection on the prose appreciation course, namely the short story material, some of the problems found in learning to write, especially writing short stories, student have not been able to meet the standards of learning to write completely. The purpose of this research is to encourage students to develop ideas and increase students creative thingking. This type of research and development. This learning module was developed using a 4-D model consisting of four stages: (1) defining, (2) designing, (3) developing, and (4) desiminating. The instrument used to collect data is in the form of a questionnaire related to the module, namely: design aspects, language aspect, and material aspects. Practicality test questionnaire and effectiveness test sheet. The results of the design validation test were declared valid and the results of the validation of linguist and materials were declarated very valid. With the level of design validity (81,25%), language (89,78%), and material (95,45%). The average overall scor is 88,82% with a very valid category. The practicality test obtained from the lecturers with a score of 94,44 and the practicality test by 11 students got an average score of 92,51 in the very pratical category. The effectiveness testwast carried out by giving a written test to students with an average score of 84,54 with a very pratical category. So the use of the development of the short story writing module is declared valid, practical, effective, and feasible to use.